Reliability analysis applied to structural ceramic blocks - Souza, Daniel de Andrade; Barboza, Aline da Silva Ramos; Lima Junior, Eduardo Toledo de (Ambiente Construído, 2018)
The Brazilian National Standard for structural masonry considers the compressive strength as the most important factor for design of structures. For the use of ceramic blocks, NBR 15812-1 (ABNT, 2010) recommends that the prism/wall efficiency factor should be at least 0.70. For that, it is important to assess the geometrical and mechanical properties of blocks and the mechanical properties of mortar, as the failure mechanism of prisms is associated with internal stresses in the brick-mortar interface. Although this design strategy has been successfully implemented, it does not consider a series of uncertainties in the production of the block and in the masonry construction process. Taking this into consideration, this paper aims to provide a statistical and reliability assessment of blocks produced by a specific manufacturer, between February and April 2014. Experimental measurements and tests provided data to a statistical characterization of dimensional parameters and compressive strength. A reliability-based evaluation was then carried out to describe the probabilistic performance of masonry subjected to compression by using First Order Reliability Method (FORM) and Monte Carlo simulation.